2005
DOI: 10.1002/cncr.21584
|View full text |Cite
|
Sign up to set email alerts
|

L‐asparaginase as a marker of chemotherapy dose modification in children with acute lymphoblastic leukemia

Abstract: BACKGROUND The objective of the current study was to compare chemotherapy dose modifications in obese (a body mass index [BMI] > 95%) and nonobese (a BMI ≤ 95%) pediatric patients with acute lymphoblastic leukemia (ALL). METHODS The study cohort was comprised of 199 pediatric patients diagnosed with ALL who were treated at 1 of 2 South Texas pediatric oncology centers between 1990–2000. The relative chemotherapy dose modification during the induction phase of chemotherapy was calculated as the ratio of 1) the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
1
0
2
Order By: Relevance
“…The study concluded that normalization of dose based on body surface area was appropriate in the pediatric patients studied. A statistical analysis using linear regression was performed to compare chemotherapy dose modifications in obese and non-obese pediatric patients with acute lymphoblastic leukemia (ALL) [117]. Obese ALL children were reported to have a 7% decrease in the mean relative modification of L-asparaginase compared with non-obese children.…”
Section: Resultsmentioning
confidence: 99%
“…The study concluded that normalization of dose based on body surface area was appropriate in the pediatric patients studied. A statistical analysis using linear regression was performed to compare chemotherapy dose modifications in obese and non-obese pediatric patients with acute lymphoblastic leukemia (ALL) [117]. Obese ALL children were reported to have a 7% decrease in the mean relative modification of L-asparaginase compared with non-obese children.…”
Section: Resultsmentioning
confidence: 99%
“…5 Perbedaan dosis lebih besar pada pasien usia 10-18 tahun dibandingkan di bawah 10 tahun; hal ini mungkin disebabkan oleh tingginya IMT, sehingga diperlukan dosis yang lebih besar. 5,20 Obesitas dapat meningkatkan risiko terjadinya LLA terkait beberapa mekanisme, yaitu melalui peningkatan hormon endogen seperti hormon seks steroid, insulin, dan insulin growth factor-1. 5 Hal ini disebabkan oleh penumpukan lemak tubuh yang berperan dalam mengontrol pertumbuhan, diferensiasi dan metabolisme sel.…”
Section: Prognosis Penderita Lla Dengan Obesitasunclassified
“…Hal ini mungkin disebabkan oleh tingginya IMT pada anak usia 10-18 tahun sehingga modifikasi dosis menjadi lebih besar. 7 Obesitas meningkatkan risiko untuk menderita kanker. Beberapa mekanisme yang dianggap berperan adalah meningkatnya hormon endogen (hormon sex steroids, insulin dan insulin growth fasctore-1) karena adanya akumulasi lemak tubuh yang berperan penting dalam mengontrol pertumbuhan, diferensiasi dan metabolisme sel.…”
Section: Diskusiunclassified